Highly Regioselective Arylation of 1,2,3-Triazole N-Oxides with Sodium Arenesulfinates via Palladium-Catalyzed Desulfitative Cross-Coupling Reaction - Zhu, Jiayi; Chen, Yu; Lin, Feng; Wang, Baoshuang; Huang, Qing; Liu, Liangxian (Synlett, 2015)
A convenient and highly regioselective palladium-catalyzed direct C5-arylation of 1,2,3-triazole N-oxides was developed in the presence of silver carbonate and tripotassium phosphate. This protocol allowed use of sodium arylsulfinates, diphenylphosphine oxide, and triphenylphosphine as arylating reagents to produce 2-aryl-5-aryl-1,2,3-triazole N-oxides in good to excellent yields, providing a complement to the existing methods for the direct arylation of 1,2,3-triazole N-oxides.
Keywords: palladium; 1,2,3-triazole N-oxide; arylation; sodium arylsulfinate